The plant-specific ABERRANT GAMETOGENESIS 1 gene is essential for meiosis in rice. (6th October 2019) - Chang, Zhenyi; Xu, Chunjue; Huang, Xiaoyan; Yan, Wei; Qiu, Shijun; Yuan, Shuting; Ni, Haoling; Chen, Shujing; Xie, Gang; Chen, Zhufeng; Wu, Jianxin; Tang, Xiaoyan
Abstract: Meiotic recombination plays a central role in maintaining genome stability and increasing genetic diversity. Although meiotic progression and core components are widely conserved across kingdoms, significant differences remain among species. Here we identify a rice gene ABERRANT GAMETOGENESIS 1 ( AGG1 ) that controls both male and female gametogenesis. Cytological and immunostaining analysis showed that in the osagg1 mutant the early recombination processes and synapsis occurred normally, but the chiasma number was dramatically reduced. Moreover, OsAGG1 was found to interact with ZMM proteins OsHEI10, OsZIP4, and OsMSH5. These results suggested that OsAGG1 plays an important role in crossover formation. Phylogenetic analysis showed that OsAGG1 is a plant-specific protein with a highly conserved N-terminal region. Further genetic and protein interaction analyses revealed that the conserved N-terminus was essential for the function of the OsAGG1 protein. Overall, our work demonstrates that OsAGG1 is a novel and critical component in rice meiotic crossover formation, expanding our understanding of meiotic progression. This study identified a plant-specific gene ABERRANT GAMETOGENESIS 1 that is required for meiotic crossover formation in rice. The conserved N-terminus of the AGG1 protein was found to be essential for its function.